2021
DOI: 10.1159/000518633
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Associations of Weight Misperception with Healthy Lifestyle among Adults in Saudi Arabia

Abstract: <b><i>Introduction:</i></b> Obesity affects more than one-quarter of adults in Saudi Arabia and is on the rise. A significant proportion of overweight and obese individuals misperceive their weight, and this misperception can affect their likelihood to exercise, consume healthy foods, or change unhealthy dietary habits. This study examines the prevalence of weight misperceptions in a national sample of Saudi adults and explores weight misperception association with sociodemographic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
4
17
3
Order By: Relevance
“…BMI is an important factor associated with self-weight perception. In accordance with other research among adults in Saudi Arabian, Malaysia, and adolescents in Wuhan, China [ 17 19 ], our findings indicated that obese populations were more likely to misperceive their weight than respondents with normal BMI levels. This indicates that obese populations may generate a new criterion for weight status besides the actual standard, while obesity is considered as “overweight” or even “normal” in their opinion, which made a vicious circle and a barrier to maintaining weight that should be a social concern.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BMI is an important factor associated with self-weight perception. In accordance with other research among adults in Saudi Arabian, Malaysia, and adolescents in Wuhan, China [ 17 19 ], our findings indicated that obese populations were more likely to misperceive their weight than respondents with normal BMI levels. This indicates that obese populations may generate a new criterion for weight status besides the actual standard, while obesity is considered as “overweight” or even “normal” in their opinion, which made a vicious circle and a barrier to maintaining weight that should be a social concern.…”
Section: Discussionsupporting
confidence: 92%
“…The above conclusions suggest that implementing health education and improving cognitive levels can effectively avoid weight misperception. The results also revealed that males were less likely to misperceive their weight than females [ 17 , 23 ]. In the internet age, females are more likely to be influenced by appearance and weight anxiety from the internet and persuaded to lose weight though they are normal even underweight.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that individuals with comorbidities are more likely to perceive a need to lose weight is at odds with previous findings that weight misperception was more common in those with a diagnosed chronic condition [36], though it is again important to make the distinction between weight perception and perceived need to lose weight. Neither the present nor afore mentioned studies collected data on the date of development of comorbid diseases in relation to weight status, therefore interpreting these findings is problematic.…”
Section: Discussioncontrasting
confidence: 75%
“…These were older age, being male, non-white, and not married or cohabiting, having no formal qualifications (compared to having a degree), having cancer that had spread, having no comorbidities (compared to having 3 or more comorbidities), and having received chemotherapy. Previous studies have identified associations between older age [25,36], being male [25], being non-white [25], and having lower levels of education [36] in misperception, particularly underestimation, of weight status, but few studies have investigated perceived need to change weight. These factors may describe a subset of the population who are at risk of health inequalities, which may be prevented through increased awareness of own weight status, and risks associated with overweight and obesity, as well as tailored support in achieving weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to mass media has been associated with changing the idea of a perfect body shape in various Arab region countries [10][11][12]. Furthermore, a recent study in Saudi Arabia showed that 42% of participants did not have an accurate perception of their weight; 67.6% of obese participants misclassified their weight, compared to 33.9% in normal weight participants [13]. Another study in 2014 revealed that Saudi women believe that obesity attracts stigma and morally compromising activities [14].…”
Section: Introductionmentioning
confidence: 99%